Convergence of constitutive photomorphogenesis 1 and phytochrome interacting factor signalling during shade avoidance - Pacín, Manuel (2016)
Shade-avoidance responses require CONSTITUTIVE PHOTOMORPHOGENESIS 1 (COP1) but the mechanisms of action of COP1 under shade have not been elucidated. Using simulated shade and control conditions, we analysed: the transcriptome and the auxin levels of cop1 and phytochrome interacting factor 1 (pif1) pif3 pif4 pif5 (pifq) mutants; the dynamics of ELONGATED HYPOCOTYL 5 (HY5) and LONG HYPOCOTYL IN FAR-RED (HFR1) proteins; and the epistatic relationships between cop1 and pif3, pif4, pif5, hy5 and hfr1 mutations in Arabidopsis thaliana. Despite severely impaired shade-avoidance responses, only a few genes that responded to shade in the wild-type failed to do so in cop1. Shade enhanced the convergence between cop1 and pifq transcriptomes, mainly on shade-avoidance marker genes. Shade failed to increase auxin levels in cop1. Residual shade avoidance in cop1 was not further reduced by the pif3, pif4 or pif5 mutations, suggesting convergent pathways. HFR1 stability decreased under shade in a COP1-dependent manner but shade increased HY5 stability. The cop1 mutant retains responses to shade and is more specifically impaired in shade avoidance. COP1 promotes the degradation of HFR1 under shade, thus increasing the ability of PIFs to control gene expression, increase auxin levels and promote stem growth.